2010
DOI: 10.2478/s11687-010-0002-2
|View full text |Cite
|
Sign up to set email alerts
|

SSR data mined from expressed sequence tags of phytoparasitic nematodes

Abstract: SummarySSR markers have become the most popular resource for studying population genetic variation in eukaryotes. However, few studies with SSR markers have been carried out with phytoparasitic nematodes. In this study a primary survey on EST-SSRs was made utilizing bioinformatics methods to derive SSRs from expressed sequence tags (ESTs) of 16 species of PPN, which belong to 7 genera and 5 families. The results showed that trinucleotide repeats were the most abundant SSRs in coding ESTs, while tetranucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 80 publications
1
2
0
Order By: Relevance
“…The vast majority (>99%) of them are trinucleotide repeats. This result confirms a recent report indicating that trinucleotide repeats were the most abundant microsatellites in coding ESTs from 16 species of plant-parasitic nematodes belonging to seven genera, including Meloidogyne [27]. Moreover, in agreement with these authors, we found that (AAC) n repeats were the most abundant in M. incognita CDS, while (ATG) n or (TTA) n , that could act as start or stop codon, respectively, were not detected.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The vast majority (>99%) of them are trinucleotide repeats. This result confirms a recent report indicating that trinucleotide repeats were the most abundant microsatellites in coding ESTs from 16 species of plant-parasitic nematodes belonging to seven genera, including Meloidogyne [27]. Moreover, in agreement with these authors, we found that (AAC) n repeats were the most abundant in M. incognita CDS, while (ATG) n or (TTA) n , that could act as start or stop codon, respectively, were not detected.…”
Section: Discussionsupporting
confidence: 93%
“…Such a distribution bias in favour of trinucleotides has been reported for some other eukaryotes, e.g., the fungus Neurospora crassa [ 25 ] or the insect Tribolium castaneum [ 26 ]. Also, a recent data-mining analysis of ESTs from phytoparasitic nematodes, including some RKN species, showed that trinucleotide repeats were the most abundant microsatellites in coding ESTs [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…in M. artiellia, a species assumed to reproduce by both amphimix and facultative meiotic parthenogenesis (De Luca et al 2002). Recently, simple sequence repeats were identified by a bioinformatic data-mining analysis in ESTs from phytoparasitic nematodes, including some root-knot nematode species, but no information was provided about regions flanking these loci (Huang et al 2010). Here, we evaluate the feasability of microsatellite isolation by screening an enriched genomic library from M. incognita, and report the subsequent characterization of 15 microsatellite loci in this nematode.…”
mentioning
confidence: 98%